Berberine Mediates Exosomes Regulating the Lipid Metabolism Pathways to Promote Apoptosis of RA-FLS Cells - Si-Fan Guo; Zhi-Bo Wang; Dan-Dan Xie; Ying Cai; Yan Wang; Xian Wang; Qiang Yang; Ai-Hua Zhang; Shi Qiu (MDPI AG, 2024)
Objectives: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by joint damage and commonly linked to symptoms such as inflammation, swelling, and pain. Traditional Chinese Medicine offers complementary and integrative approaches in the management of rheumatoid arthritis, potentially providing additional options that may help address treatment challenges and enhance overall patient care. This paper explores the mechanism of action of berberine from the perspective of cellular exosomes by mediating exosomal contents and thus treating RA. Methods: With the help of flow cytometry and confocal laser scanning microscope, it was determined that berberine promotes apoptosis in RA-FLS cells, and then lipid metabolomics technology was applied to screen and characterize the exosomes of RA-FLS cells to identify lipid core biomarkers closely related to RA, which were then projected into various databases for comprehensive analysis. Results: The data analysis showed that berberine could call back 11 lipid core biomarkers closely associated with RA, and interactive visualization of the database revealed that these markers were mainly focused on lipid metabolism aspects such as fatty acid elongation, degradation, and biosynthesis, as well as the biosynthesis of unsaturated fatty acids or PPARA activation of gene expression, PPARα's role in lipid metabolism regulation, glycerophospholipid metabolism, mitochondrial fatty acid oxidation disorders, and organelle biogenesis and maintenance. Conclusions: Berberine exerts its therapeutic effect on RA by mediating exosomal contents and thus regulating multiple lipid-related biological pathways, affecting the PPARγ-NF-κB complex binding rate, CREB and EGR-1 expression, cellular phagocytosis, and other aspects needed to inhibit proliferation and inflammatory responses in RA-FLS. This study offers a research foundation for exploring the mechanism of action of berberine in the treatment of RA.